Nutrient supplementation and secondary metaolites in melanoma cells - Stoll, Karin Elisabeth (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1994)
Considerable interest exists with regard to the putative therapeutic role of ascorbic acid in various conditions. A condition which has received much attention is cancer, as it is reported that ascorbic acid may be a prophylactic against cancer development. However, the actual involvement of ascorbic acid, an oxidizing/reducing agent, in the development and progression of tumours is presently a subject of much speculation. This study initially addressed the effect of ascorbic acid supplementation over a nutritional concentration range (0 - 100 μg/ml) on the in vitro growth of non-malignant LLCMK and malignant B16 cells. Ascorbic acid supplementation of these two cell types resulted in an overall decrease in the growth of both types of cells. The actual inhibitory mechanism of ascorbic acid on cell growth was not clear. Further study attempted to define and explain a mechanism responsible for this effect. Ascorbic acid has a role in the maintenance of tissue integrity and host defences, thus providing a rational basis for examining its relationship to cancer. Ascorbic acid is lcnown to be essential for the structural integrity of the intercellular matrix of the cells, the latter being a complex aqueous gel containing, amongst other compounds, fats and prostaglandins. Fats and prostaglandins have diverse effects on. membrane stability, enzyme activity and secondary messengers within cells. Hence, this study investigated the effect of ascorbic acid supplementation on certain enzymes and secondary metabolites within the cells, which had the potential to be involved in the control of cell growth. Throughout this study, emphasis was placed on the Bl6 melanoma cells as ascorbic acid supplementation did not significantly affect levels of secondary metabolites within the non-malignant LLCMK cells. Ascorbic acid supplementation of the B16 cells resulted in significant increases in adenylate cyclase activity and cyclic adenosine monophosphate levels, witb a significant decrease in Bl6 cell growth in that particular experiment. As cyclic adenosine monophosphate has a regulatory role in the cell cycle, this study suggested that the inhibitory effect of ascorbic acid supplementation on cell growth was mediated tbrough a final effect provided by the second messenger, cyclic adenosine monophosphate. However, clarification of tbe mechanism of tbe effect of ascorbic acid on adenylate cyclase activity was required. Hence, a further study investigated prostaglandin E₂ levels, as tbese affect adenylate cyclase activity. Prostaglandin E₂ levels were also found to be inversely related to Bl6 cell growth with ascorbic acid supplementation. It thus appeared tbat adenylate cyclase activity was dependent on prostaglandin E₂ levels in the B16 cells, and further study showed that tbis was indeed the case. Here, higher levels of prostaglandin E₂ supplementation of the Bl6 cells inhibited cell growth significantly and also significantly increased adenylate cyclase activity. Arachidonic acid is the precursor of prostaglandin E₂. In the presence of ascorbic acid supplementation, the percentage arachidonic acid composition of the Bl6 cells was inversely correlated with cell growth. Hence, prostaglandin E₂ levels in ascorbic acid supplemented B16 cells appeared dependent on tbe amount of precursor present. This was confirmed when Bl6 cells were supplemented with arachidonic acid. The latter had an inhibitory effect on Bl6 cell growth and also stimulated prostaglandin E₂ production. The cause of tbe inverse relationship between B16 cell growth and arachidonic acid composition with ascorbic acid supplementation was furtber investigated and found to be dependent on tbe uptake of arachidonic acid and other essential fatty acids from tbe medium. The enzymes phospholipase A₂ delta-5 and delta-6-desaturase, and elongase which could influence arachidonic acid levels were not affected to any extent by ascorbic acid supplementation and therefore did not influence the inverse relationship between B16 cell growth and arachidonic acid. Hence, it can be concluded that the effect of ascorbic acid supplementation on the BI6 cells is mediated, in part at least, by cyclic adenosine monophosphate. However, this is not the result of a direct effect of ascorbic acid supplementation. The initial effect of ascorbic acid supplementation concerns fatty acid - in particular arachidonic acid - uptake from the medium, with subsequent cascade effects On secondary metabolites, ultimately affecting the cellular levels of cyclic adenosine monophosphate.
Keywords: Vitamin C -- Therapeutic use; Cancer -- Research